Hyperbaric oxygen therapy as rescue therapy for pediatric frosted branch angiitis with Purtscher-like retinopathy: A case report - Lee, Chi-Tai; Hsieh, Tzu-Han; Chu, Chan-Ching; Hsu, Yung-Ray; Wang, Jia-Horng; Wang, Jia-Kang; Zhao, Zhanqi; Chang, Hou-Tai (Frontiers in Medicine, 2023)
Introduction Frosted branch angiitis (FBA) is an uncommon uveitis characterized by fulminant retinal vasculitis. Purtscher-like retinopathy (PuR) is a rare retinal angiopathy associated with a non-traumatic etiology. Both FBA and PuR can cause profound visual impairments. Case report We describe the case of a 10-year-old male who presented with sudden bilateral painless visual loss due to FBA with concurrent PuR, with notable viral prodrome 1 month prior to presentation. Systemic investigations revealed a recent herpes simplex virus 2 infection with a high titer of IgM, positive antinuclear antibody (ANA) (1:640), and abnormal liver function tests. After administration of systemic corticosteroids, anti-viral agents, and subsequent immunosuppressive medications, the FBA was gradually alleviated. However, fundoscopy and optical coherence tomography (OCT) revealed persistent PuR and macular ischemia. Hence, hyperbaric oxygen therapy was administered as a rescue strategy, which resulted in gradual bilateral visual acuity improvement. Conclusion Hyperbaric oxygen therapy may be a beneficial rescue treatment for retinal ischemia secondary to FBA with PuR.